Trends in exercise for hypertension: a bibliometric analysis - Lou, Yan; Sun, Ning; Zhang, Min; Qiu, Yongzhen; Wang, Jie; Chen, Jiajia (Frontiers in Cardiovascular Medicine, 2023)
Objective To investigate development trends and research hotspots of exercise for hypertension research and provide researchers with fresh perspectives for further studies. Materials and methods Articles and reviews regarding exercise and hypertension spanning May 1st 2003 to May 18th 2023 were retrieved from the Web of Science Core Collection (WOSCC) database. VOSviewer and Citespace were mainly used to perform and visualize co-authorship, co-citation, and co-occurrence analysis of countries, institutions, authors, references and keywords in this field. Results A total of 1,643 peer-reviewed papers were identified, displaying a consistent increasing trend over time. The most prolific country and institution were Brazil and University of Sao Paulo, respectively. And we identified the most productive author was lrigoyen, Maria Claudia C, while Pescatello Linda S was the most co-cited author. Journal of hypertension was the most prominent journal, and Hypertension was the journal which was the most co-cited. And this field can be divided into 3 research themes: exercise interventions for hypertension, age-specific relevance of exercise for hypertension, and the global burden of hypertension and the role of exercise. According to the result of keywords analysis, epidemiological information, types of exercise, target population, mechanism, and study design are significant research areas. “Resistance training”, “adults”, and “heart rate variability” were identified as the major future research foci. Conclusions The findings offer a scientific insight into exercise for hypertension research, presenting researchers with valuable information to understand the current research status, hotspots, and emerging trends for future investigation.